Techno-economic analysis of high-efficiency natural-gas generators for residential combined heat and power. (15th September 2018) - Vishwanathan, Gokul; Sculley, Julian P.; Fischer, Adam; Zhao, Ji-Cheng
Graphical abstract: Highlights: Energy consumption analysis of 10 US cities shows 1 kWe as good residential CHP size. Widespread CHP deployment in residences requires high efficiency low cost generators. Spark spread analysis shows Northeast U.S. and California as favorable deployment sites. Widespread CHP adoption will lead to large annual energy savings and CO2 reduction. Abstract: Residential combined heat and power (CHP) systems produce electricity onsite while utilizing waste heat to supplement home heating requirements, which can lead to significant reductions in CO2 emissions and primary energy consumption. However, the current deployment of such CHP systems in the U.S. residential sector is extremely low primarily due to their high cost, short system life, and low system efficiency. Based on an analysis of average energy consumption of representative single-family homes in 10 U.S. cities across 7 different climate zones, it is concluded that there is no one-size-fits-all residential CHP system, but that a range of products are more likely to reflect consumer preferences. It is further identified via a systematic techno-economic analysis (TEA) that high-efficiency (e.g., 30–40% fuel to electricity), long-life (e.g., 15 years), low-cost (preferably less than U.S. $2, 500 installed price), and low emissions are key requirements to enable widespread deployment of CHP systems in the U.S. residential sector. This article analyzes how the payback period would change for each city by varying nearly a dozen parameters and concludes with an evaluation on maximum market penetration based on a given set of parameters, and the resulting energy and emissions savings that can be practically achieved in some scenarios.